Adherence to guidelines for incidental pulmonary nodules: insights from a Nordic survey - Kirill Neumann; Janna Berg; Haseem Ashraf; Johan Isaksson; Aija Knuuttila; Morten H. Borg; Torben R. Rasmussen (Acta Oncologica)
Background and purpose: There is limited data on the real-world management of incidental pulmonary nodules (IPN). In this article, we review current practices and adherence to international guidelines in the Nordic countries.